Kinerja Organisasi Pada Instansi Pemerintah: Bagaimana peran dari Capital Intellectual? - Amrie Firmansyah; Elzami Haqie Ednoer; Friska Dwi Enita (JRAK: Journal of Accounting Research and Computerized Accounting, 2022)
Intellectual capital as an intangible asset that has not been regulated in financial accounting standards has been reviewed in recent decades. In the public sector, intellectual capital review and testing are still limited. This study aims to examine the effect of intellectual capital on organizational performance. This study uses primary data sourced from questionnaire surveys to the Directorate General of Taxes employees, namely Account Representatives. The questionnaire survey was conducted online from 17 to 21 January 2022. Hypothesis testing was carried out using multiple linear regression tests. This study concludes that public organizational capital, public social capital, and relational public capital positively affect organizational performance. Meanwhile, technological public capital has a negative effect on organizational performance, and public human capital does not influence organizational performance. This study shows public sector organizations to include intellectual capital components in improving employee development policies and planning to improve organizational performance.